Financial autonomy of the Slovenian local government - Haček, Miro (Journal of comparative politics, 2020)
Slovenia is one of the very few countries in the European Union with a single tier local government system, and while levels of local democracy have been on the rise since gaining independence in 1991, relations between the state on the one side and local governments (municipalities) on the other has slowly deteriorated, especially over the questions of municipal competencies and financing of local communities. While Slovenia ratified the European Charter on Local Self-Government (ECLG) in 1996, the charter was never fully implemented, as the subsidiarity principle was never fully implemented. The paper is analysing the issue of local autonomy with an emphasis on the financial autonomy, using primary and secondary sources as well as empirical data from national and local authorities.
Keywords: Autonomy; Avtonomija; Finance; Local self-government; Lokalna samouprava